Food for thought. Issue 1 (1st January 2016) - Prosser, Bill
Not seeing things might seem a surprise in the visual arts, yet it happens all the time. This article brings attention to some ignored items under our noses – food leftovers – and suggests a context and perspective as to why they are well worth our undivided consideration.